Assessment of flavaglines as potential chikungunya virus entry inhibitors. (March 2015) - Wintachai, Phitchayapak; Thuaud, Frédéric; Basmadjian, Christine; Roytrakul, Sittiruk; Ubol, Sukathida; Désaubry, Laurent; Smith, Duncan R.
ABSTRACT: Chikungunya virus (CHIKV) is a re‐emerging mosquito‐borne alphavirus that recently caused large epidemics in islands in, and countries around, the Indian Ocean. There is currently no specific drug for therapeutic treatment or for use as a prophylactic agent against infection and no commercially available vaccine. Prohibitin has been identified as a receptor protein used by chikungunya virus to enter mammalian cells. Recently, synthetic sulfonyl amidines and flavaglines (FLs), a class of naturally occurring plant compounds with potent anti‐cancer and cytoprotective and neuroprotective activities, have been shown to interact directly with prohibitin. This study therefore sought to determine whether three prohibitin ligands (sulfonyl amidine 1 m and the flavaglines FL3 and FL23) were able to inhibit CHIKV infection of mammalian Hek293T/17 cells. All three compounds inhibited infection and reduced virus production when cells were treated before infection but not when added after infection. Pretreatment of cells for only 15 minutes prior to infection followed by washing out of the compound resulted in significant inhibition of entry and virus production. These results suggest that further investigation of prohibitin ligands as potential Chikungunya virus entry inhibitors is warranted.